Aristotelian Physical Address and Heart Doença na Atualidade - Neves, Afonso Carlos; Tavares de Azevedo, Paulo Guilherme (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2015)
During the 1970 and 1980 decades, studies on pathophysiology of heart failure arrived to the conclusion that some information from physical examination had great prognostic value within the evaluation of these patients. The gradual compound of these elements made it possible to set four “profiles” of people with acute heart failure, known as “warm and dry”, “warm and wet”, “cold and dry” and “cold and wet”, which correspond, respectively, to the states of high perfusion-without edema, high perfusion-with edema, low perfusion-without edema and low perfusion-with edema. However, the use of the terms “warm”, “cold”, “dry” and “wet” to assess pathological states was part of the scientific discourse of Antiquity and of the Aristotle work indeed. Through a historic and sociologic analysis of the period in which each discourse was developed, we achieve to make hypothesis for the comings and goings processes of these terms.